Mutu Fisik Bubuk Kunyit (Curcuma longga Linn) Hasil Metode Foam-mat Drying Menggunakan Oven Microwave - Dhinar Patliani; Dian Purbasari (Jurnal Agritechno, 2021)
Turmeric (Curcuma longa L) in Indonesia is widely known as a herbal medicinal plant, food coloring, and food flavoring. The high water content of turmeric will shorten the storage time and the quality of the ingredients. The need for drying which is the process of removing the moisture content of the material with the aim of prolonging the shelf life. The use of the foam-mat drying method with the addition of adhesives aims to speed up the drying process and maintain the quality of a material. The result of drying turmeric obtained is turmeric powder product. This study used a completely randomized design (CRD) with two factors, namely the variation of the microwave oven power and the composition of the developer agent (ovalet). The research procedure was divided into two stages, namely the manufacture of powder and continued with the measurement of physical quality. The stages of making powder begin with the preparation of raw materials, stripping, size reduction, addition of developer, drying, then grinding. The second stage is measuring physical quality, namely fineness modulus, average grain size, powder moisture content, color, water absorption, oil absorption, and bulk density. The power variations used are 420 watts, 535 watts, and 680 watts, while the composition of the developer is 1%, 2%, and 4%. Data analysis using two-way ANOVA statistical test with two factors that affect the variation of power and composition of the developer (ovalet). FM values ​​ranged from 0.364 – 1.576, D values ​​ranged from 0.005 – 0.0012 mm, final moisture content values ​​ranged from 7.60 – 9.59%, powder moisture content values ​​ranged from 9.47 – 11.43%ww , L values ​​ranged from 61.46 – 65.96, a values ​​ranged from 13.54 – 16.05, b values ​​ranged from 48.21 – 52.42, DSA values ​​ranged from 2.78 – 3.54 ml/ g, DSM values ​​ranged from 1.22 – 1.60 ml/g, and DC values ​​ranged from 0.38 – 0.44 g/cm3. The combination treatment of drying power with developer is influenced by the drying power of the parameters, namely the value of moisture content, fineness modulus, average grain size, brightness level, redness level, yellowness level, oil absorption, water absorption, and bulk density. While the developer affects the finenes modulus, average grain size, yellowness level, and bulk density.